2016
DOI: 10.1136/vr.103549
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin I in three cat breeds with hypertrophic cardiomyopathy

Abstract: Part of the troponin I data reported in this study has been previously published as the baseline data in a prospective cohort study: Langhorn and others (2014).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Regarding the distribution of cTnI in healthy cats, a previous study found that neither sex nor age significantly affected the cTnI concentration in 35 healthy cats; also, the concentration was not affected by breed (British Shorthairs, Maine Coons, and Norwegian Forest Cats). 17 We studied a large population of healthy cats and found that the cTnI concentration varied significantly by body weight. One possible explanation for this finding is that heavier cats may exhibit more ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the distribution of cTnI in healthy cats, a previous study found that neither sex nor age significantly affected the cTnI concentration in 35 healthy cats; also, the concentration was not affected by breed (British Shorthairs, Maine Coons, and Norwegian Forest Cats). 17 We studied a large population of healthy cats and found that the cTnI concentration varied significantly by body weight. One possible explanation for this finding is that heavier cats may exhibit more ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a highly sensitive immunoassay for cTnI, the ADVIA Centaur CP TnI-Ultra assay (Siemens Healthineers Japan, Tokyo, Japan), has been described. 16,17 It is a 3-site, second generation sandwich immunoassay employing direct chemiluminometry; the lower limit of cTnI detection is 0.006 ng/mL. Compared with the conventional assay, 13,14 the cTnI assay allows highly sensitive evaluation of a specific marker of low-grade myocardial injury.…”
Section: In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Feline hypertrophic cardiomyopathy appears to have a breed predisposition, as does canine DCM and is, reportedly, the most common cardiac disorder in cats and has shown remarkable similarities to human HCM [ 19 ]. The familial predisposition is most obvious in Maine Coon, Ragdoll, and British and American Shorthair breeds [ 23 , 24 , 25 ]. Separate genetic mutations have been identified as causal of HCM in the Maine Coon and Ragdoll breeds within the MYBPC3 gene [ 24 , 26 ] but there are also affected individuals within the Maine Coon breed lacking the mutation, indicating that there are additional causes of the disease to be established [ 27 ].…”
Section: Hypertrophic Cardiomyopathy (Hcm)mentioning
confidence: 99%
“…This is important, considering that an estimated 35% of human cases are caused by MYBPC3 mutations [ 16 ]. Higher concentrations of cTnI have also been observed in some breeds of cats with HCM [ 25 , 29 ], but no mutations have been observed in that gene in Maine Coons or British Shorthairs [ 25 ], whereas mutations in this gene have been observed in humans. Pigs also appear to have a heritable form of HCM, but no specific genetic associations have been discovered to date [ 30 ].…”
Section: Hypertrophic Cardiomyopathy (Hcm)mentioning
confidence: 99%